HYGIENIC ASPECTS OF IMPROVING WORKING CONDITIONS FOR MEDICAL PERSONNEL - Tashpulatova M.N (Western European Studies, 2025)
The article examines the issues related to the psychological and emotional strain that may arise as a result of the high workload and intensity of modern medical work, the increase in occupational risk, as well as the challenges of ensuring effective working conditions within the healthcare system. These problems have a direct impact on the work efficiency and overall health of medical professionals. Therefore, conducting scientifically grounded research aimed at improving their working conditions, reducing psychological and emotional stress, and minimizing occupational risks is considered both urgent and highly significant.
Keywords: medical personnel; occupational workload; mental-emotional stress; preventive measures